2002
DOI: 10.1076/orbi.21.1.43.2603
|View full text |Cite
|
Sign up to set email alerts
|

Epiphora due to compression of the lacrimal sac by a supernumerary blind sac

Abstract: A 23-year-old male had suffered from epiphora in the left eye since childhood. There was no history of infection or trauma. A supernumerary punctum was seen in the left lacrimal caruncle on examination. Subsequent dacryocystography and computer tomography showed a blind-ended sac that was connected to the supernumerary punctum, but not to the normally developed nasolacrimal system. When distended with secretion, this blind-ended lacrimal sac caused compression and obstruction of the normal lacrimal drainage pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Although only the latter type has been described, 14 the former membranous septum is first reported in the present study to our knowledge. This type may be a congenital anomaly of the lacrimal sac, such as known entities of the diverticula, fistula, and supernumerary sacs, 15,16 as the anomaly was similarly shown on both sides. The partitions do not appear to make a closed space, which is similar to the previous study, 14 because no mucinous pooling is seen in the specimens.…”
Section: Discussionmentioning
confidence: 90%
“…Although only the latter type has been described, 14 the former membranous septum is first reported in the present study to our knowledge. This type may be a congenital anomaly of the lacrimal sac, such as known entities of the diverticula, fistula, and supernumerary sacs, 15,16 as the anomaly was similarly shown on both sides. The partitions do not appear to make a closed space, which is similar to the previous study, 14 because no mucinous pooling is seen in the specimens.…”
Section: Discussionmentioning
confidence: 90%
“…The resultant canaliculitis with its surrounding edema caused obstruction of the lacrimal drainage; hence epiphora. 2 Epiphora however, may develop despite patent lacrimal drainage system. The 2-compartment model for lacrimal canalicular drainage of Kakizaki et al , suggested that the muscle of Duverney-Horner may deviate normal flow within the accessory canaliculus and thence transport tears back to the lacrimal tear lake, leading to epiphora.…”
Section: Discussionmentioning
confidence: 99%
“…17 A supernumerary punctum connected to a supernumerary canaliculus and ending in a blind supernumerary sac is extremely rare. 18 Caruncular abnormalities, including bilobed caruncles and ectopic caruncles, have been described in patients with Goldenhar syndrome, 19 which is a congenital disorder believed to be caused by the defective development of the first and second brachial arches and the first brachial cleft during the fourth through eighth weeks of embryologic development.…”
Section: Congenital Tumoursmentioning
confidence: 99%